DESIGN METHOD OF FLEXIBLE AND THIN TUBE SHEET AND RESEARCH OF STRUCTURE SIZE BASED ON ANSYS - JIANG XiaoZhi; DONG JinShan; LV DongXiang (Jixie qiangdu)
On the basis of the specific calculation example,the flexible and thin tube sheet was designed with methods of different countries respectively. Comparing the calculation results,the advantages and disadvantages of each design method can be evaluated. In order to study the main parameters,such as the thickness of tube sheet,the center distance of heat exchange tube and the radius of transition fillet,which influence the stress distribution characteristics of flexible and thin tube sheet,the tube sheet was analyzed by finite element software ANSYS. Finally,the appropriate structure dimension was confirmed.